Perkembangan Penelitian Pembelajaran Sains di Sekolah Dasar: Sebuah Analisis Bibliometrik - Mahmudi, Moh Rosyid; Prayitno, Mulyo; Hartono, Deni Puji (Musamus Journal of Primary Education, 2024)
This research is a bibliometric analysis. Meta data analyzed by bibliometric analysis is meta data of documents on "science learning in elementary schools". The purpose of this study is to determine and describe the development of "science learning in elementary schools" research that has existed to date. The method used is mixed method by combining bibliometric analysis and explanatory analysis. Meta data documents are taken from the Scopus website. An initial search with more general keywords resulted in 197,454 documents. Then filtered and selected based on criteria that reinforce that the selected documents are the results of research on science learning in elementary school and the final meta data number is 138 documents. The results of bibliometric analysis assisted by biblioshiny application show that research on this topic has started in 1956 and continues to grow rapidly until now. This study also shows data that the Jurnal Pendidikan IPA Indonesia is the largest publisher of articles on science learning in elementary schools. And at the end of the analysis shows related topics and recommendations that research on science learning in elementary schools is still very relevant and has a fairly low density. And at the end of the analysis shows related topics and recommendations that research on science learning in elementary schools is still very relevant and has a fairly low density.